Characteristics of the board of directors’ members and their relationship with strategic decisions to raise funds: evidence in companies listed on BM&FBovespa - Andrade dos Santos, Edicreia; Lara, Flávio Luiz; Mendes de Oliveira, Renata; Lunkes, Rogério João (Contextus - Revista Contemporânea de Economia e Gestão, 2017)
The board of directors’ members have an important role for the management of strategies and fundraising as well as they represent an important mechanism of corporate governance, which can influence the company’s performance. In this context, the object of this study is to verify the relation between the observable characteristics of the board of directors and the results of the indicators coming from the strategies and decisions associated to fundraising. The data were obtained from 60 companies with shares in the BM&FBovespa stock exchange between 2011 and 2015. Among the results it is observed that the adjusted and dry capitalization variables present a more significant relation with the variables related to the characteristics of the administrative council’s managers. It was also possible to identify the necessity to diversify the characteristics of the members in the top management, considering the small participation of women and the predominance of older managers.